Strongyloides stercoralis - a Legacy from the Past - Inês Chora; Rodrigo Pimentel; Fernando Friões; Paula Dias; Sérgio Silva (European Journal of Case Reports in Internal Medicine, 2015)
The authors present the case of a 65-year-old Caucasian man who had previously lived in Guinea-Bissau. The patient was diagnosed in Portugal with an anti-neutrophil cytoplasmic antibody-associated vasculitis and started on corticosteroids plus cyclophosphamide, with clinical improvement. Some months later, his general status deteriorated, iatrogenic bicytopenia developed and immunosuppressive drugs were tapered. Microbiological tests identified numerous larvae and eggs of Strongyloides stercoralis in various biological samples, and a diagnosis of hyperinfection syndrome was established. The patient was started on antihelminthic drugs but developed septic shock and died. This case highlights a rare and severe complication of immunosuppression in developed countries.